Predictive role of SLC1A5 in neuroblastoma prognosis and immunotherapy - Jian Cheng; Miaomiao Sun; Xiao Dong; Yang Yang; Xiaohan Qin; Xing Zhou; Yongcheng Fu; Yuanyuan Wang; Jingyue Wang; Da Zhang (BMC Cancer)
Abstract Background Neuroblastoma, a prevalent extracranial solid tumor in pediatric patients, demonstrates significant clinical heterogeneity, ranging from spontaneous regression to aggressive metastatic disease. Despite advances in treatment, high-risk neuroblastoma remains associated with poor survival. SLC1A5, a key glutamine transporter, plays a dual role in promoting tumor growth and immune modulation. However, its contributions to neuroblastoma biology remain largely unexplored. Methods This study utilized clinical neuroblastoma samples from 20 patients and 1310 cases from four public datasets to investigate SLC1A5 expression, biological function, and prognostic significance. Differential expression, Kaplan–Meier survival analysis, gene set enrichment analysis, and weighted correlation network analysis were conducted. Functional validation included qPCR, immunohistochemistry, Western blotting, and cell proliferation assays using the SLC1A5 inhibitor V-9302. A prognostic signature, SRPS, was constructed and validated using machine-learning approaches. Immune infiltration analysis was performed to evaluate the tumor immune microenvironment. Results SLC1A5 expression was significantly elevated in high-risk neuroblastoma and correlated with advanced stages and poor prognosis. GSEA revealed mTORC1 signaling enrichment in high SLC1A5 expression groups, validated by increased p-p70S6K levels in tumor samples and neuroblastoma cells. V-9302 treatment suppressed mTORC1 signaling and inhibited cell proliferation. Hub-genes were identified to form the SRPS model, which demonstrated superior prognostic performance compared to existing models. Immune infiltration analysis revealed a more immunosuppressive tumor microenvironment associated with high SLC1A5 expression. Additionally, SLC1A5 negatively regulated ST8SIA1, a gene crucial for GD2 biosynthesis, suggesting that SLC1A5 inhibition may enhance GD2-directed immunotherapies. Conclusion SLC1A5 plays a pivotal role in neuroblastoma by promoting tumor progression and shaping an immunosuppressive microenvironment. The SRPS model, incorporating SLC1A5-associated genes, offers robust prognostic utility. Targeting SLC1A5 through advanced drug delivery systems and combined metabolic-immunotherapeutic strategies may enhance treatment specificity and efficacy. These findings provide a foundation for novel therapeutic approaches to improve outcomes in high-risk neuroblastoma patients.